用于伤口治疗的组合物和方法 (2024)
本发明公开了用于治疗伤口的组合物包括共价连接的氧化石墨烯(GO)和透明质酸(HA)，XAV939，和水。该组合物还可包含表面活性剂，例如PEG。可以将组合物局部施用于对象以治疗对象的伤口。还提供了使用该组合物治疗伤口的方法。 A composition for treating a wound includes graphene oxide (GO) and hyaluronic acid (HA) that are covalently linked, XAV939, and water. The composition can also include a surfactant, such as PEG. The composition can be topically administered to a subject to treat a wound of the subject. Methods of treating a wound using the composition are also provided.